APPLICATION DU MODELE INVERSE AUX INTERACTIONS EAU-ROCHE DANS LES EAUX SOUTERRAINES DES METAGRANODIORITES, SUD-EST COTE D’IVOIRE - Oga, Yéï Marie Solange; Adiaffi, Bernard; Gnamba, Franck Maxime; Marlin, Christelle; Baka, Derving; Amani, Etche Mireille Elise; Biémi, Et Jean (European Scientific Journal, ESJ, 2015)
In Ivory Cost, few studies have been performed on the process of water-rock interactions in aquifers of basement. The study aim is to provide, from an inverse model by usgs program “phreeqci”, orders of magnitude of the mass transfer from each mineral during the process of water mineralization in the aquifer of metagranodiorites. We use mineralogy and geochemistry of water and rocks. The mineralogical study indicated paragenesis of plagioclase-feldspar-chlorite-biotite and amphibole. Kaolinite is assumed to be the clay product of silicate minerals hydrolysis in the study area. The simulation provided dissolution rate of 8.3 10-4 mol l-1 for plagioclase, 1.7 10-4 mol l-1 for chlorite, 9.4 10-5 mol l-1 for biotite and 2.3 10- 5 mol l-1 for amphibole during water-rock interaction process occurred 15,000 years ago.